COMPUTER GRAPHICS PROGRAMS AND PROCESSES OF THEIR APPLICATION TO ENGINEERING GRAPHICS (Modern American Journal of Engineering, Technology, and Innovation, 2025)
At any time, students' learning of various subjects has been considered a form of meeting their demand for information. At the present time, when educational reforms are being implemented step by step in our republic, based on the requirements of the national personnel training program and the main goal of the reform, students of educational institutions should be able to independently perform certain educational tasks, search for and analyze the necessary information, training and formation and development of the skills of accepting responsible solutions on this basis is a task